2016
DOI: 10.1186/s40794-016-0031-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccination for international travelers to Asia

Abstract: There is a wide range in prevalence of hepatitis B virus (HBV) infection and HBV immunization programs between different regions. Hepatitis B is a vaccine preventable disease yet is still endemic in the majority of countries in Asia. Despite the decreasing global prevalence of chronic HBV infection, there is still considerable risk of HBV infection among international travelers to high endemic areas. Numbers of international travelers are expected to increase year by year; thus immunization among this cohort i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
(38 reference statements)
0
7
0
1
Order By: Relevance
“…These countries have achieved more than 70% coverage of completed HBV vaccination (China, 99%; Thailand, 99%; Cambodia, 97%; Vietnam, 95%; the Philippines, 79%; Uzbekistan, 82%, Mongolia, 76%). 28 29 30 31 Therefore, the prevalence of anti-HBs gradually increased in East, Southeast, and Central Asia after implementation of universal HBV vaccination program.…”
Section: Discussionmentioning
confidence: 99%
“…These countries have achieved more than 70% coverage of completed HBV vaccination (China, 99%; Thailand, 99%; Cambodia, 97%; Vietnam, 95%; the Philippines, 79%; Uzbekistan, 82%, Mongolia, 76%). 28 29 30 31 Therefore, the prevalence of anti-HBs gradually increased in East, Southeast, and Central Asia after implementation of universal HBV vaccination program.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of HBV in travelers is through percutaneous or mucosal exposure to HBV-infected blood or bodily fluids including saliva or semen [30,31]. There are reports of transmission via sexual contact, contaminated blood and its products, and contaminated medical equipment and through sharing of infected needles and injecting apparatus [31,32].…”
Section: How Hbv Infection Is Transmittedmentioning
confidence: 99%
“…Hepatitis B is one of the most common vaccine-preventable travel-associated infectious diseases. It is estimated that approximately 240 million people worldwide are infected with hepatitis B virus (HBV) and approximately 1 million people die each year from HBV-related illness [73]. The risk of acquiring HBV during the travel is relatively low (about 0.2 to 0.6 per 1000 person-months).…”
Section: Travel-related Vaccinesmentioning
confidence: 99%
“…However, the risk of chronic HBV infection in people over 40 years of age is lower in comparison to young adults (6% vs. 8%) [76]. The hepatitis B vaccine is recommended to all unvaccinated travellers going to regions with intermediate to high prevalence of chronic hepatitis B; however, only 15-30% of international travellers had received a full vaccination course prior to travel [73]. The Swiss study showed that hepatitis B vaccination was administered significantly less often to senior travellers [5].…”
Section: Travel-related Vaccinesmentioning
confidence: 99%